Past, Present, and Future of Dynamic Kidney and Liver Preservation and Resuscitation. Issue 9 (1st April 2016) - Jochmans, I.; Akhtar, M. Z.; Nasralla, D.; Kocabayoglu, P.; Boffa, C.; Kaisar, M.; Brat, A.; O'Callaghan, J.; Pengel, L. H. M.; Knight, S.; Ploeg, R. J.
Abstract : The increased demand for organs has led to the increased usage of "higher risk" kidney and liver grafts. These grafts from donation after circulatory death or expanded criteria donors are more susceptible to preservation injury and have a higher risk of unfavorable outcomes. Dynamic, instead of static, preservation could allow for organ optimization, offering a platform for viability assessment, active organ repair and resuscitation. Ex situ machine perfusion and in situ regional perfusion in the donor are emerging as potential tools to preserve and resuscitate vulnerable grafts. Preclinical findings have ignited clinical organ preservation research that investigates dynamic preservation, its various modes (continuous, preimplantation) and temperatures (hypo‐, sub, or normothermic). This review outlines the current status of dynamic preservation of kidney and liver grafts and describes ongoing research and emerging clinical trials. Abstract : The authors summarize recent advances in the field of dynamic preservation of kidneys and livers, and detail ongoing and upcoming research that will advance the field.